2018
DOI: 10.3892/etm.2018.6880
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of hydrogen gas inhalation on a murine model of allergic rhinitis

Abstract: Allergic rhinitis (AR) is a common chronic inflammatory condition. It has been previously indicated that oxidative stress may contribute to allergic inflammation, including AR. Although molecular hydrogen (H2), an antioxidative agent, has been effective in treatment of numerous oxidative stress-associated diseases, the effect of inhalation of a high concentration of H2 on AR remains unknown. In the current study, female BALB/c mice were sensitized with ovalbumin (OVA) followed by intranasal OVA challenge to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The health benefits include improving mood, reducing anxiety, and counteracting an overactive sympathetic nervous system [ 1 ]. In terms of disease prevention and treatment, H 2 has been used to treat many diseases, including lifestyle diseases [ 2 ]; immune diseases, such as atopic dermatitis [ 2 ], hay fever [ 3 ], and chronic rheumatoid arthritis [ 4 ]; respiratory diseases, such as asthma [ 5 ], chronic obstructive pulmonary disease [ 6 ], and pneumonia caused by the coronavirus disease 2019 (COVID-19) [ 7 ]; neurological diseases, such as depression [ 8 ], dementia [ 9 ], stroke [ 10 ], post-cardiac arrest syndrome [ 11 , 12 ], subarachnoid hemorrhage [ 13 ], and traumatic injury from blast shock waves [ 14 ]; myocardial infarction [ 15 - 17 ]; chronic kidney disease [ 18 ]; sepsis [ 19 ] and hemorrhagic shock [ 20 , 21 ]; and cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The health benefits include improving mood, reducing anxiety, and counteracting an overactive sympathetic nervous system [ 1 ]. In terms of disease prevention and treatment, H 2 has been used to treat many diseases, including lifestyle diseases [ 2 ]; immune diseases, such as atopic dermatitis [ 2 ], hay fever [ 3 ], and chronic rheumatoid arthritis [ 4 ]; respiratory diseases, such as asthma [ 5 ], chronic obstructive pulmonary disease [ 6 ], and pneumonia caused by the coronavirus disease 2019 (COVID-19) [ 7 ]; neurological diseases, such as depression [ 8 ], dementia [ 9 ], stroke [ 10 ], post-cardiac arrest syndrome [ 11 , 12 ], subarachnoid hemorrhage [ 13 ], and traumatic injury from blast shock waves [ 14 ]; myocardial infarction [ 15 - 17 ]; chronic kidney disease [ 18 ]; sepsis [ 19 ] and hemorrhagic shock [ 20 , 21 ]; and cancer [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported the use of histological and cellular factor analyses to evaluate the effect of hydrogen on ovalbumin-induced sinus mucosal inflammatory reaction (allergic rhinitis, AR) in mice. The results showed that hydrogen inhalation significantly alleviated the symptoms of sneezing and pruritus, reduced the infiltration of inflammatory cells into the mucosa, and decreased the levels of IL-5, IL-13, and MCP-1 in serum, indicating the value of hydrogen in treating allergic diseases (Fang et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…With the support of hydrogen inhaler AMS-H-01/AMS-H-03 provided by Asclepius Meditec Co., Ltd., tens of animal studies or pilot clinical trials based on inhaled gas which combines H 2 (concentration of ~66%) with O 2 (concentration of ~34%) were accomplished and published. 14 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 Additionally, recent formal clinic trials based on the same inhaler AMS-H-01/AMS-H-03 also revealed positive results in respiratory diseases, such as allergic rhinitis, asthma, chronic obstructive pulmonary disease, etc. Especially, it is recommended to use the mixed gas of 66.6% H 2 /33.3% O 2 for treating coronavirus disease-19 (COVID-19) patients as described in the Diagnosis and Treatment Protocol for Novel Coronavirus Pneumonia, 7 Edition released by National Health Commission of China, 55 and such guideline is also republished in English by the World Health Organization China Office.…”
Section: Introduction Of H Ydrogen B Iomedicinementioning
confidence: 99%